EARLY RECOGNITION OF DEPRESSION AMONG ADOLESCENTS IN JUNIOR HIGH SCHOOL: A MIX-METHOD STUDY IN LOW-INCOME POPULATIONS SETTING - I Made Peri Ardiana Kusuma; Anak Ayu Sri Wahyuni; Jeikawati Jeikawati; Nyoman Ari Yoga Wirawan (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Depression is a prevalent mental health problem among adolescents and poses significant risks to emotional, social, and academic functioning, particularly in low-income settings where access to mental health services is often limited. This study aimed to identify depressive symptoms among junior high school adolescents and explore their causal beliefs, defense mechanisms, and help-seeking behaviors. A sequential explanatory mixed-methods design was employed among students at SMP Satu Atap (SATAP) Tianyar Barat, Karangasem Regency. Depressive symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9), followed by in-depth interviews with adolescents scoring ≥10 to provide a deeper understanding of the psychosocial factors underlying quantitative findings. A total of 67 adolescents participated. Depressive symptoms were categorized as minimal (43.3%), mild (28.4%), moderate (19.4%), moderately severe (6.0%), and severe (3.0%). Female students and seventh-grade students showed a higher risk of moderate-to-severe depressive symptoms. Interviews with 17 adolescents revealed that family relationship problems, lack of social support, and economic hardship were the most frequently perceived causes of depression. Isolation, repression, and acting out emerged as the dominant defense mechanisms. These findings highlight the importance of school-based mental health screening and psychosocial support programs to facilitate early identification and targeted interventions for adolescents at risk of depression. ABSTRAK Depresi merupakan masalah kesehatan mental yang umum terjadi pada remaja dan dapat berdampak pada prestasi akademik, hubungan sosial, serta kualitas hidup. Risiko depresi cenderung lebih tinggi pada remaja yang hidup di lingkungan berpendapatan rendah sehingga deteksi dini diperlukan untuk mendukung intervensi yang tepat. Penelitian ini bertujuan mengidentifikasi gejala depresi pada remaja sekolah menengah pertama serta mengeksplorasi keyakinan penyebab, mekanisme pertahanan diri, dan perilaku mencari pertolongan. Penelitian menggunakan metode mixed-method dengan desain sequential explanatory pada siswa SMP Satu Atap (SATAP) Tianyar Barat, Kabupaten Karangasem. Gejala depresi diukur menggunakan Patient Health Questionnaire-9 (PHQ-9), kemudian dilanjutkan dengan wawancara mendalam untuk memperdalam pemahaman mengenai faktor-faktor yang melatarbelakangi depresi pada remaja dengan skor PHQ-9 ≥10. Sebanyak 67 remaja berpartisipasi. Gejala depresi diklasifikasikan sebagai minimal (43,3%), ringan (28,4%), sedang (19,4%), sedang berat (6,0%), dan berat (3,0%). Remaja perempuan dan siswa kelas VII memiliki risiko lebih tinggi mengalami gejala depresi sedang hingga berat. Wawancara terhadap 17 remaja menunjukkan bahwa masalah keluarga, kurangnya dukungan sosial, dan kesulitan ekonomi merupakan faktor yang paling sering dikaitkan dengan depresi. Temuan ini menegaskan pentingnya skrining kesehatan mental berbasis sekolah untuk mendukung deteksi dini dan intervensi bagi remaja berisiko.